Digital Storytelling as a Narrative Health Promotion Process: Evaluation of a Pilot Study. (April 2016) - DiFulvio, Gloria T.; Gubrium, Aline C.; Fiddian-Green, Alice; Lowe, Sarah E.; Del Toro-Mejias, Lizbeth Marie
Digital storytelling (DST) engages participants in a group-based process to create and share narrative accounts of life events. The process of individuals telling their own stories has not been well assessed as a mechanism of health behavior change. This study looks at outcomes associated with engaging in the DST process for vulnerable youth. The project focused on the experiences of Puerto Rican Latinas between the ages of 15 to 21. A total of 30 participants enrolled in a 4-day DST workshops, with 29 completing a 1 to 3-minute digital story. Self-reported data on several scales (self-esteem, social support, empowerment, and sexual attitudes and behaviors) were collected and analyzed. Participants showed an increase in positive social interactions from baseline to 3-month post workshop. Participants also demonstrated increases in optimism and control over the future immediately after the workshop, but this change was not sustained at 3 months. Analysis of qualitative results and implications are discussed.